2020
DOI: 10.1136/ijgc-2020-001724
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sentinel node mapping with intracervical indocyanine green injection for endometrial cancer: the SENTIFAIL study – a multicentric analysis of predictors of failed mapping

Abstract: ObjectivesLaparoscopy is commonly used for endometrial cancer treatment, and sentinel lymph node (SLN) mapping has become the standard procedure for nodal assessment. Despite the standardization of the technique, there is no definitive data regarding its failure rate. The objective of this study is to identify factors associated with unsuccessful SLN mapping in endometrial cancer patients undergoing laparoscopic SLN mapping after intracervical indocyanine green (ICG) injection.MethodsWe retrospectively evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…As already noticed by and Sozzi et al. ( 35 ) (age ≥ 65 OR: 1.8, 95% CI: 1.14–2.98, p = 0.012) and Tortorella et al. ( 20 ) (OR: 1.41 per 10-year increase in age, 95% CI: 1.08–1.84; p = 0.01), older age was linked to unsuccessful mapping but only at univariate analysis.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As already noticed by and Sozzi et al. ( 35 ) (age ≥ 65 OR: 1.8, 95% CI: 1.14–2.98, p = 0.012) and Tortorella et al. ( 20 ) (OR: 1.41 per 10-year increase in age, 95% CI: 1.08–1.84; p = 0.01), older age was linked to unsuccessful mapping but only at univariate analysis.…”
Section: Discussionsupporting
confidence: 70%
“…These two histopathological features, meanwhile represent independent predictors for mapping failure, as already emphasized by Sozzi et al. ( 35 ).…”
Section: Discussionmentioning
confidence: 63%
“…At present, lymph vascular space invasion (LVSI), non-endometroid histology is seen as independent risk factors for failed mapping ( 75 ). The false negative SLN was more likely to appear in unilateral mapping failure patient.…”
Section: The Diagnostic Accuracy Of Slnmmentioning
confidence: 99%
“…When we analysed the factors that potentially infl uence bilateral SLN detection in the entire cohort, we found that age was the only patient-related signifi cant variable, confi rmed at multivariable analysis. Most of the studies previously reported other variables signifi cantly related with bilateral SLN mapping, such as use of ICG, low BMI, no clinically enlarged lymph nodes, early FIGO stage, no lysis of adhesions at the beginning of surgery and surgeon's experience in SLN biopsy (Eriksson et al, 2016;Tanner et al, 2015;Tortorella et al, 2019;Body et al, 2018;Harold et al, 2019;Sozzi et al, 2020). The relationship between increased age and lymphatic dysfunction has been described: in particular, cell senescence, impaired contractile function and decrease of nitric oxide in aged lymphatic collectors, may lead to poor drainage of lymph, causing bilateral mapping failure (Shang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%